Cyclic compression of mesenchymal stem cells loaded scaffolds for bone tissue engineering - Guo, Fangfang (2015)
Cyclic mechanical loading on Mesenchymal Stem Cells (MSCs) has resulted in increased expression of early osteogenic markers as well as increased mineralized matrix deposition. In most of past studies, scaffolds were subjected to the cyclic loading immediately after seeding or a few days after static culture. However, sufficient cell numbers and stable attachment of cells could enhance better mechanotransduction and accelerate bone formation. The aim of the study was to investigate the osteogenic responses of well proliferated human fetal mesenchymal stem cells (hfMSC) seeded scaffolds to cyclic compression loading, using biaxial rotating bioreactor to proliferate the cells first and the mini static bioreactor to induce appropriate load and strain. Preliminary study was done to investigate the most effective strain that enhances bone formation of hfMSCs. Preliminary study demonstrated that cyclic compression at physiological related strain (2,200 μɛ) best enhances osteogenesis and proliferation of hfMSCs, and this strain was applied in the second study. Results in the second study showed that proliferation was inhibited in the loaded group in a short-term culture (7 days) while enhanced in long-term (14 days). ALP activity was enhanced (1.35 fold) in cyclic loaded group at day 14, which in turn result in promoted mineralization. Conclusion can be drawn that cyclic compression enhances the osteogenesis and mineralization on well proliferated cellular scaffolds.